Numerical study of the inner canalization geometry optimization in a milling tool used in micro quantity lubrication. (8th August 2014) - Duchosal, A.; Serra, R.; Leroy, R.
<x content-type="archive" xml:space="preserve">Abstract</x> This study focused on numerical analysis of the parameters influencing the oil mist flow (MQL) outside a rotating tool, in non-contact configuration. This approach was a mandatory step for the parameter optimizations before taking into account the material removing. The optimization of inner canalization geometries to a milling tool was performed to transfer the oil mist. The Reynolds Average Navier Stokes (RANS) and Lagrangian equations were used to simulate the oil mist flow inside the canalizations by integrating the standard k-ε turbulence model with the STAR CCM+ commercial software. The dynamic numerical calculation was used to optimize the inner canalizations of a milling tool. Because of the particular external tool shape, the micro spray cooling is not guaranteed to reach the cutting edge. The external tool geometry, the inlet pressure, the shape and the orientation of the inner canalization geometries in the tool body and the rotation speed have significant influence on the lubrication efficiency. The main goal of this study was to improve this efficiency as function of these parameters. Thus, parameter sets giving good lubrication were determinate for a type of tool.